2010
DOI: 10.1111/j.1365-2516.2010.02357.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived competence in children and adolescents with haemophilia: an explorative study

Abstract: With the introduction of prophylaxis, restricting children with haemophilia to participate in physical activities was no longer necessary. Subsequently, many studies report on improved physical functioning in children and adolescents with haemophilia. However, little is known about psychological aspects such as perceived competence and impact of disease. Therefore, the aims of this study were to explore: (i) perceived competence, (ii) perceived impact of illness, and (iii) analyse associations between perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 29 publications
1
38
0
1
Order By: Relevance
“…Although females can be symptomatic hemophilia carriers, hemophilia is almost exclusively limited to boys. 148 Although medical advances have increased opportunities for youth with bleeding disorders to lead more normal physical lives, 145,148 youth with bleeding disorders continue to face social challenges and warrant additional investigation with regard to social adjustment and bullying. 143 Youth with bleeding disorders used to be discouraged from physical activities because of the risk of uncontrolled bleeding.…”
Section: Inherited Bleeding Disordersmentioning
confidence: 99%
“…Although females can be symptomatic hemophilia carriers, hemophilia is almost exclusively limited to boys. 148 Although medical advances have increased opportunities for youth with bleeding disorders to lead more normal physical lives, 145,148 youth with bleeding disorders continue to face social challenges and warrant additional investigation with regard to social adjustment and bullying. 143 Youth with bleeding disorders used to be discouraged from physical activities because of the risk of uncontrolled bleeding.…”
Section: Inherited Bleeding Disordersmentioning
confidence: 99%
“…Although the only previous study to examine self-competence in children with pacemakers found no significant differences in functioning compared to that of healthy peers, 9 most of the research with other pediatric populations has consistently shown significantly lower levels of perceived selfcompetence in various domains. 14,23 The conflicting evidence between findings in this study and the only other study to examine self-competence in children with pacemakers 9 may be explained in several ways. First, it is possible that the illness status and medical history of pacemaker recipients in this study is different than that of the sample collected by Alpern et al 9 Advances in device technology and medical and diagnostic techniques over the past few decades have resulted in greater number of patients receiving pacemakers, 24,25 suggesting that different types of heart dysfunctions that were previously untreated with pacing are currently being addressed with pacemaker technology.…”
Section: Discussionmentioning
confidence: 45%
“…27 Our findings are also consistent with previous research demonstrating significant relationships between higher self-competence and better functioning in HRQOL-related domains in children with hemophilia, such as the ability to participate in activities with peers. 23 All self-competence domains were significantly and positively correlated with the Social HRQOL domain, suggesting that self-competence may have the strongest role in protecting pediatric pacemaker recipients against lower social functioning. It is possible that children's belief in their ability to successfully engage in a variety of activities, including social interactions, prepares them to better cope with the challenges that they may face as a result of their illness.…”
Section: Discussionmentioning
confidence: 98%
“…A review of titles and abstracts revealed that only few studies published before 2012 were relevant to our research focus. We therefore limited the search to 2012‐2017 but kept nine older articles deemed to be informative to our purpose . Subsequently, we excluded studies not including YWH in PTX, studies focusing on low‐income country issues, on female patients or those with inhibitor or HIV/hepatitis C infection issues.…”
Section: Methodsmentioning
confidence: 99%
“…The present qualitative review examined adherence to PTX in YWH . We aimed to gain comprehensive insight into main drivers and barriers to adherence by exploring them in the context of YWH's disease perceptions, characteristics, health‐related QoL and needs . The outcome is an overview of the latest published recommendations to support treatment adherence in YWH during the transition from family‐oriented care to self‐care and from paediatric to adult care.…”
Section: Introductionmentioning
confidence: 99%